Prevalence, knowledge, attitudes and practices towards body art in university students: body art as an indicator of risk taking behaviours? (Italian Journal of Public Health, 2010)
Background: Young people are attracted by body art and consider it as a way of being “different”. Body art(tattoos, piercing, etc.) represents an important socio-cultural phenomenon which is not risk free for health.Existing literature, moreover, points out that deviant behaviours and unhealthy lifestyles are significantlyassociated with body art.Objective and methods: The research was aimed to describe the knowledge, attitudes, and practices ofuniversity students towards body art, highlighting the association between body art and some demographicvariables, deviant behaviours, unhealthy lifestyles, knowledge of health risks and medical complicationspotentially involved. Data came from a cross-sectional study conducted on a sample, selected at random, of1.200 undergraduate university students, (570, human sciences; 630, scientific areas). The instrument for thesurvey was a 21 item multiple choice questionnaire. Data was codified and statistical analysis was computedthrough Epi-Info and Openstat software.Results: Students from a scientific background showed a higher rate of interest, (p
Keywords: body piercing; tattooing; body art; health risk; risk-taking behaviours